“Does he need help or can he help himself?” Preschool children’s expectations about others’ instrumental helping versus self-helping - Kim, Sunae; Sodian, Beate; Paulus, Markus (Frontiers in Psychology, 2014)
In the present study, we investigated a total of fifty-one 3.5-, 4.5-, and 5.5-year-old children’s expectations about another person’s helping behaviors. We asked children to complete a story in which one person failed to complete his goal (e.g., because an object was misplaced or put out of his reach) while the other person observed the event. We asked whether the children expected the other person to help the protagonist or whether they expected the protagonist to help himself. Children of 3.5 years expected the other person to provide help in the majority of trials. In contrast, the older children were equally likely to predict that the other person would help the protagonist or the protagonist would help himself.